Effets De La Digestion Gastrique Sur Les Propriétés Anthelminthiques De Zanthoxylum Zanthoxyloides (Lam.) Zepernick & Timlerto Et De Newbouldia Laevis (P.Beauv.) Sur Haemonchus Contortus - Sidi, Irvine Yèinou Minaflinou Sacca; Alowanou, Géorcelin Goué; Tchétan, Esaïe; Aminou, Maliki Youssouf; Hounzangbé-Adoté, Sylvie Mawulé; Babatoundé, Séverin (European Scientific Journal, ESJ, 2017)
Several recent studies have shown that medicinal plants Zanthoxylum zanthoxyloides (Fagara) and Newbouldia laevis possess anthelmintic activities in vitro on different stages of development of gastrointestinal nematodes. The objective of this study was to evaluate the in vitro anthelmintic properties of residues from digestion in the rumen of leaf powders of both plants on the migration of the 3rd-stage larvae L3s of Haemonchus contortus. Residues obtained after incubation at 0 h, 24 h and 96 h kinetic points of the leaf powders of both plants in the rumen of sheep with fistulae were used for the assay. The larval migration inhibition test evaluated the anthelmintic properties of the methanolic extracts of residues of the two plants. The effect of plant extracts on larval migration was notdose- dependent (p> 0.05) but was a function of plant incubation time (p 0.05). N. Laevis seems to have retained his anthelmintic property after incubation in sacco in the rumen. On the other hand, Fagara seems to lose its effectiveness as it stays in the rumen. Findings obtained on these plants confirm their traditional use in veterinary medicine especially in the control of helminthiasis.